The Actual and Potential Prospects for the Inclusion of Migrant Workers in the Labor Market (On Example of St. Petersburg) - Anatoly Vladimirovich Klyuev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the analysis of the inclusion of migrants to labor activity taking into account the real needs of the labour market and targeted approach to their recruitment, as well as revealed an effective mechanism for attracting labour migrants in accordance with the real needs of businesses in the form of organized recruitment of foreign workers that can be used in regions with low employment potential. The study of complex of measures on improvement of regulation of labor migration in the aspect of formation of the effective mechanism of attracting skilled workers from migrant workers to provide basic sectors of economy in labor force (by example of St. Petersburg).